2018
DOI: 10.3233/nha-170030
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome and aging: Physiological and mechanistic insights

Abstract: The development of human gut microbiota begins as soon as the neonate leaves the protective environment of the uterus (or maybe in-utero) and is exposed to innumerable microorganisms from the mother as well as the surrounding environment. Concurrently, the host responses to these microbes during early life manifest during the development of an otherwise hitherto immature immune system. The human gut microbiome, which comprises an extremely diverse and complex community of microorganisms inhabiting the intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
382
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 527 publications
(399 citation statements)
references
References 199 publications
8
382
2
7
Order By: Relevance
“…The change of microbial composition is always accompanied with significant functional alteration . Although Lactobacillus and Bifidobacterium treatment affected different aspects of functions in gut microbiota, the anti‐aging effects of both probiotics were similar in our study, suggesting different probiotic strains may act through different mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The change of microbial composition is always accompanied with significant functional alteration . Although Lactobacillus and Bifidobacterium treatment affected different aspects of functions in gut microbiota, the anti‐aging effects of both probiotics were similar in our study, suggesting different probiotic strains may act through different mechanisms and pathways.…”
Section: Discussionmentioning
confidence: 50%
“…Various theories have been proposed for the cause of aging, suggesting that different and complicated mechanisms underlie the process of aging . Studies have found that oxidative stress, DNA damage, and inflammation play pivotal roles in age‐associated decline of physiological, genomic, metabolic, and immunological functions . Therefore, anti‐aging therapy and agents targeting these theories are developed, which have dramatically improved human life expectancy .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 16,165 ] In line with this, alterations in the intestinal epithelial physiology, as well as gut microbiota composition and metabolite production, accompany the aging process. [ 166,167 ] Accumulating evidence suggests the aged intestinal epithelium—instead of being hypo‐proliferative as suggested by instinct—contains more proliferating cells and has a higher proliferation rate. [ 168–171 ] Concomitantly, there is also an increase in apoptosis in the stem cell population, [ 170,171 ] and a retarded response to fasting or irradiation‐induced damage.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…[ 174,175 ] Multiple factors contribute to these age associated changes in gut microbiota and its metabolic repertoire, including changes in lifestyle, dietary habits, lack of mobility, compromised immunity, and reduced intestinal functionality. [ 167 ] Rampelli et al., for example, found that microbial genes for tryptophan metabolism, involved in the production of indole derivatives or other tryptophan metabolites, are enriched in aged groups compared to young controls. [ 18 ] Apart from microbial pathways, the main host mechanism for tryptophan metabolism is the kynurenine pathway that degrades tryptophan to kynurenine via the enzyme indoleamine 2,3‐dioxygenase (IDO).…”
Section: Conclusion and Prospectsmentioning
confidence: 99%